The relative centrality of life domains among secular, traditionalist and Ultra-Orthodox (Haredi) men in Israel. Issue 1 (1st January 2021) - Sharabi, Moshe; Kay, Avi
ABSTRACT: The Ultra-Orthodox population is the fastest growing population in Israel and this study is the first to examine the relative centrality of life domains among Ultra-Orthodox men in Israel and compare them with secular and traditionalist men. The participants were 206 secular, 98 traditional, and 199 Ultra-Orthodox employed Israeli men. While previous literature found that higher levels of religiosity were associated with lower work centrality, in this pioneering study no differences were found among secular, traditionalist, and Ultra-Orthodox men with regards the centrality of work in their lives. In addition, no differences were found among the groups with regard to the centrality of community and family. With that, as expected, centrality of religion increased with increasing level of religiosity. Finally, the centrality of leisure was highest among secular and the lowest among Ultra-Orthodox employees. Overall, demographic variables have a low capability of explaining life domains centrality among the three groups. The meaning and importance of these findings are discussed in the paper.